2018
DOI: 10.1161/hypertensionaha.118.11465
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistopathology and Steroid Profiles Associated With Biochemical Outcomes After Adrenalectomy for Unilateral Primary Aldosteronism

Abstract: Unilateral primary aldosteronism (PA) is the most common surgically curable form of hypertension that must be accurately differentiated from bilateral PA for therapeutic management (surgical versus medical). Adrenalectomy results in biochemical cure (complete biochemical success) in almost all patients diagnosed with unilateral PA; the remaining patients with partial or absent biochemical success comprise those with persisting aldosteronism who were misdiagnosed as unilateral PA preoperatively. To identify det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 32 publications
7
43
1
1
Order By: Relevance
“…Williams et al recently reported that this hybrid steroid was significantly higher in peripheral and adrenal plasma from patients with KCNJ5-mutated than patients with other causes of PA, suggesting the usefulness of selective steroid profiling for PA [62]. Moreover, the peripheral steroid profiles and histologic features (including APA, hyperplasia and APCC) of unilateral PA patients who underwent adrenalectomy contributed to the predicted postoperative biochemical outcome [60]. APA harboring KCNJ5 mutations principally display a lipid rich clear cell (ZF-like) histology, whereas APA with CACNA1D, ATP1A1, and ATP2B3 mutations predominantly show a compact cell (ZG-like) predominate histology [63][64][65][66][67].…”
Section: Steroid Biome Of Apccmentioning
confidence: 98%
See 2 more Smart Citations
“…Williams et al recently reported that this hybrid steroid was significantly higher in peripheral and adrenal plasma from patients with KCNJ5-mutated than patients with other causes of PA, suggesting the usefulness of selective steroid profiling for PA [62]. Moreover, the peripheral steroid profiles and histologic features (including APA, hyperplasia and APCC) of unilateral PA patients who underwent adrenalectomy contributed to the predicted postoperative biochemical outcome [60]. APA harboring KCNJ5 mutations principally display a lipid rich clear cell (ZF-like) histology, whereas APA with CACNA1D, ATP1A1, and ATP2B3 mutations predominantly show a compact cell (ZG-like) predominate histology [63][64][65][66][67].…”
Section: Steroid Biome Of Apccmentioning
confidence: 98%
“…Steroid profiling using liquid chromatography-tandem mass spectrometry (LC-MS/MS) has evolved as a useful method for subtype classification of PA [57][58][59][60][61]. In particular, 18-oxocortisol has been previously reported as a biomarker for the differential diagnosis of PA [61].…”
Section: Steroid Biome Of Apccmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear discriminant analysis (LDA) was performed using MATLAB R2017b software on the combined cohort (n = 380 patients) employing linear combinations of variables to maximize the separation between groups by increasing precision estimates by variance reduction 26,27 . LDA models have been widely exploited in the context of prediction modelling for clinical research as described previously [28][29][30][31][32] . In the model used herein, the algorithm computes a set of coefficients for linear Table 2, whereas normalized coefficients are represented in Figure 1C.…”
Section: Linear Discriminant Analysismentioning
confidence: 99%
“…A semiautomated rotation microtome (Microm HM 355S, Thermo Fisher Scientific) was used to cut 3-μm tissue microarray sections that were transferred to glass slides for IHC and H&E staining. IHC staining was performed under standardized conditions on a Discovery XT automated stainer (Ventana Medical Systems, Roche Diagnostics) using monoclonal antibodies directed against human (h) CYP11B1, CYP11B2, CYP17A1 (43), and HSD3B1 (22), developed by one of the co-authors (CGS). Slides were incubated with primary antibodies (rat monoclonal anti-hCYP11B1 [1:20], mouse monoclonal anti-hCYP11B2 [1:100], mouse monoclonal anti-17α-hydroxylase [1:500], mouse monoclonal anti-hHSD3B1 [1:500], or rabbit polyclonal anti-hHSD3B2 [1:250] (Abcam, Ab154385), in Dako REAL antibody dilution, Agilent) and detected by the Discovery DAB Map Kit (Ventana Medical Systems, Roche Diagnostics), including incubation with respective secondary antibodies (against CYP11B2, HSD3B1, and HSD3B2: antimouse and antirabbit, ready-to-use universal secondary antibody, 760-4205, Ventana Medical Systems, Roche Diagnostics; against CYP11B1: antirat, ready-to-use universal secondary antibody, BA-4000, Vector Laboratories).…”
Section: Dna Sequencingmentioning
confidence: 99%